Photoshop 7 trade secrets. - Aronoff, Janee, ....-; Cromhout, Gavin, ....-; Cross, David, ....- (Birmingham : Friends of ED, 2002)
1.Efficiency 2.Selection secrets 3.Layers 4.Retouching 5.Special effects 6.Web graphics 7.Setting up 8.Hardware
Keywords: Beeldbewerking; Computer graphics; Photoshop